Global impacts of Covid-19 on lifestyles and health and preparation preferences: an international survey of 30 countries - Li, Jiaying; Fong, Daniel Yee Tak; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Pandian, Vinciya; Davidson, Patricia M; Duan, Wenjie; Tarrant, Marie; Lee, Jung Jae; Lin, Chia-Chin; et al. (Edinburgh University Global Health Society, 2023)
Background: The health area being greatest impacted by coronavirus disease 2019 (COVID-19) and residents' perspective to better prepare for future pandemic remain unknown. We aimed to assess and make cross-country and cross-region comparisons of the global impacts of COVID-19 and preparation preferences of pandemic.